INFORMATION AND COMMUNICATION TECHNOLOGY IN EDUCATIONAL MANAGEMENT INFORMATION SYSTEM (MIS) - Siti Dewi Kurniasih (Indonesian Journal of Islamic Communication, 2023)
The development of Information and Communication Technology (ICT) has brought significant changes in various sectors, including education. Management Information Systems (MIS) in the education sector utilize ICT to increase efficiency in data management, administration and learning processes. This paper discusses the role of ICT in supporting educational SIM, starting from managing academic information, communication between stakeholders, to personalizing the teaching and learning process. The application of ICT in education has great potential to increase accessibility, transparency and collaboration between system users. However, the application of ICT also faces several challenges, such as the digital divide, limited training for teaching staff, and issues of data privacy and security. This research uses descriptive-qualitative methods to identify the benefits and obstacles in implementing ICT in education SIM. From the results of the analysis, it can be concluded that optimizing ICT in education SIM requires continuous support, such as HR training, infrastructure improvements, strict data security policies, as well as efforts to build a culture of innovation. It is hoped that the appropriate use of ICT in education SIM can improve the quality of the education system as a whole, prepare students to face challenges in the digital era, and support a more inclusive and effective learning process.